Analisis Relevansi Anggaran Komprehensif dan Anggaran Parsial dalam Menghadapi Dinamika Lingkungan Bisnis Modern: Studi Literatur - Jessyka Aulia; Mawar Indah Juita Hutagalung (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
The current business environment is characterized by considerable uncertainty, high volatility, complexity, and ambiguity. Mass layoffs in the Indonesian textile industry, government budget cuts, and a shift in global investment focus toward artificial intelligence have cast doubt on the relevance of conventional budgeting models. The purpose of this literature study is to conduct a comparative analysis between comprehensive budgeting and partial budgeting in addressing changes in the modern business environment. The method used is a literature review evaluating various academic journals and related news sources. The findings of the study indicate that comprehensive budgeting is superior in terms of integrated planning, performance control, and coordination between organizational units, making it more effective in stable environments. On the other hand, partial budgeting is found to be more flexible and adaptable to changes, especially for short-term decisions, although it lacks integration between functions. No single approach is clearly superior to the other. A hybrid approach combining both models is recognized as the most relevant solution in these uncertain times, as it allows organizations to balance systematic strategic planning with operational flexibility. This study recommends that organizations adapt their budgeting systems according to the complexity and dynamics of the business environment they face.